Advanced distillation technologies design, control and applications - Kiss, Anton Alexandru (Chichester [England] : Wiley, 2013)
"Covers the background, recent developments, fundamental principles, design and simulation, detailed cases of separations in DWC, and future trends"--
Basic concepts in distillation -- Design, control, and economics of distillation -- Dividing-wall column -- Optimal operation and control of DWC -- Advanced control strategies for DWC -- Applications of dividing-wall columns -- Heat pump assisted distillation -- Heat-integrated distillation column -- Cyclic distillation -- Reactive distillation.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Distillation; Electronic books